PENGARUH AUDIT OPERASIONAL DAN IMPLEMENTASI STRATEGI PEMASARAN TERHADAP EFEKTIVITAS PENJUALAN PADA PT SEAWEED INDONESIA - I Putu Evan T Darsanofa; Tiara Kusuma Dewi (Universitas Triatma Mulya, 2023)
Operational audit is an examination of the company's operational activities, including accounting policies and operational policies that have been determined by management, to find out whether the operational activities have been carried out effectively, efficiently, and economically. This study aims to examine the effect of operational audits and implementation of marketing strategies on sales effectiveness at PT Seaweed Indonesia. The number of respondents used in the study were 35 people. The research method used is quantitative research and data analysis using multiple regression analysis. The results of the study stated that the operational audit had a positive and significant effect on the sales effectiveness of PT. Indonesian Seaweed with a significance value of 0.011 < 0.05. And the implementation of the strategy has a positive and significant effect on the sales effectiveness of PT. Indonesian Seaweed with a significance value of 0.000 <0.05